Effect of exercise-induced dehydration on time-trial exercise performance: a meta-analysis. - Goulet ED (British Journal of Sports Medicine, 2011)
Objective To use the meta-analytical procedures to determine the magnitude of the effect of exercise-induced dehydration (EID) upon time-trial (TT) exercise performance. Methods Studies were located via database searches and cross-referencing. TT performance outcomes were converted to mean percentage changes in power output. Random-effects model meta-regressions, analogue to the ANOVA and weighted mean effect summaries were used to delineate the effect of the EID-associated body weight (BW) loss on TT performance. Results Five research articles, all using cycling TTs, were included, producing 13 effect estimates and representing 39 subjects. The mean ambient temperature, relative humidity, exercise intensity and duration of the exercise trials were 26.0±6.7°C, 61±9%, 68±14% of VO2max and 86±34 min, respectively. The effect of EID (mean BW loss of 2.20±1.0%) during self-paced exercise conditions was to produce a non-significant increase in endurance performance of 0.06±2.72% (p=0.94), compared with the maintenance of euhydration (mean BW loss of 0.44±0.48%). Meta-regression analyses revealed a statistically significant relationship between the percentage changes in power output and exercise intensity and duration, but not with the EID-associated percentage changes in BW loss. Drinking according to the dictate of thirst was associated with an increase in TT performance compared with a rate of drinking below (+5.2±4.6%, p=0.01) or above (+2.4±5.0%, p=0.40) thirst. The probability that drinking to thirst confers a real and meaningful advantage on TT performances conducted under field conditions compared with a rate of drinking below and above thirst sensation is of the order of 98% and 62%, respectively. Conclusions (1) Compared with euhydration, EID (up to 4% BW loss) does not alter cycling performances during out-of-door exercise conditions; (2) exercise intensity and duration have a much greater impact on cycling TT performances than EID and; (3) relying on thirst sensation to gauge the need for fluid replacement maximises cycling TT performances.